New Syllabus Mathematics for class 1 - Wong Oon Hua; Wong Oon Hua (Singapore Oxford University, 2025)
New Syllabus Primary Mathematics (NSPM) is a comprehensive series of textbooks and workbooks that adopts the Concrete-Pictorial-Abstract approach. The (C-P-A) approach forms an integral part of the learning process. NSPM incorporates the use of concrete aids and manipulatives..